Student Active Participation in the Study of the Light Bulbs - Ogrutan, Petre; Elena Aciu, Lia; Sandu, Florin; Gerigan, Carmen (UIKTEN, 2016)
The paper presents an initiative approach to the study of light bulbs, involving active participation of the students engaged in interactive problem-/project-based learning of electromagnetic compatibility and energetic efficiency belonging to the environmental issues. The paper includes preliminary and complementary simulations of the hardwarefirmware-software-netware development of a laboratory test bench for the study of conducted perturbations generated during the bulb firing sequence. This laboratory sub-system is useful both in association with traditional methods of learning as well as with e-Learning platforms. Finally, the paper presents the results of a concise survey of opinions on the outcomes of this research.
TEM Journal; Vol 5, No 4, 2016. ISSN 2217-8309